Association between MDR1 C3435T polymorphism and colorectal cancer risk: A meta-analysis. Issue 51 (December 2017) - Jin, Shan-Shan; Song, Wei-Juan
Abstract: Background: The multidrug resistance gene 1(MDR1) C3435T polymorphism has been reported to be associated with colorectal cancer (CRC) risk in Asians, however the results were inconsistent. Thus, we performed a meta-analysis to generate large-scale evidence on the association between C3435T polymorphism and CRC risk in Asian populations. Methods: The PubMed, Web of Science, Embase, CNKI, and Chinese Biomedicine databases were searched up to January 15, 2017. The odd ratios (ORs) and 95% confidence intervals (95% CIs) were calculated by a fixed-effects or random-effects model. Sensitivity and cumulative meta-analysis were also performed. Results: A total of 7 studies involving 4818 individuals were included in this pooled-analysis. The results suggested that persons carrying a T allele at the C3435T polymorphism had a significantly decreased risk of CRC in Asian population (T vs C: OR = 0.897, 95%CI = 0.826–0.975, P = .01), and the significant association was also observed in another 2 genetic models (TT vs CC: OR = 0.721, 95%CI = 0.605–0.861, P < .001; TT vs TC+CC: OR = 0.679, 95%CI = 0.579–0.795, P < .001). Moreover, the results of sensitivity and cumulative meta-analysis indicated the stable of our results. Finally, funnel plot and Egger's test showed no evidence of publication bias. Conclusions: In summary, this meta-analysis provided evidence that MDR1 C3435T polymorphism is associated with a decreased risk of CRC in Asian population.